Human Resource Practices and Innovative Work Behavior: Examining the Role of Psychological Safety - Akhmad, Jaenudin; Damiyana, Damdam; Makmuroh, Umi Hanik; Karomah, Nurul Giswi; Nurlia, Titim (SAFE-Network, 2026)
This study examines the relationship between human resource practices and innovative work behavior, with psychological safety as a mediating variable. The research aims to explain how organizational human resource systems influence employees’ innovative behavior through the development of a psychologically safe work environment. A quantitative approach was employed using a survey method. Data were collected from 150 employees working in medium and large organizations across various sectors. The data were analyzed using descriptive statistics, reliability and validity testing, and regression-based mediation analysis. The results indicate that human resource practices have a positive and significant effect on innovative work behavior. Human resource practices also significantly influence psychological safety, which in turn positively affects innovative work behavior. Mediation analysis confirms that psychological safety partially mediates the relationship between human resource practices and innovative work behavior. These findings suggest that innovation at the employee level is driven not only by formal human resource systems but also by employees’ perceptions of interpersonal safety within the organization. The study highlights the importance of integrating supportive human resource practices with efforts to foster a psychologically safe work climate in order to sustain innovative work behavior. The findings contribute to the literature on human resource management and organizational innovation and provide practical implications for managers seeking to enhance employee-driven innovation.